The Relation between Body Mass Index and Retinal Photoreceptor Morphology and Microvascular Changes Measured with Adaptive Optics (rtx1) High-Resolution Imaging - Anna Zaleska-Żmijewska; Zbigniew Wawrzyniak; Magdalena Kupis; Jacek P. Szaflik (Journal of Ophthalmology)
Background. Overweight and obese patients are at risk for diabetes, cardiovascular disorders, and microvascular complications. The rtx1TM (Imagine Eyes, France) is a microscope that allows near histological visualizations of cones and retinal microcirculation. Objective. This study analysed the cones and retinal microvascular changes in a group of 47 healthy women with different BMI values. Participants were divided into 2 groups: the BMI group (28 women with BMI >/25) and the control group (19 lean women with BMI <25). Results. The lumen and diameter of retinal arteries were not significantly different between groups. There were significant differences in the thickness of arteriole walls. The WLR and WCSA values differed significantly between the control and BMI groups (for WLR 0.25 ± 0.03 vs. 0.29 ± 0.03, p<0.001; for WCSA 4136.7 ± 1140.0 vs. 5217.3 ± 944.0, respectively, p<0.001). In healthy eyes, cone density and morphology were not affected by weight. Conclusions. Retinal image analysis with rtx1 offers a novel noninvasive measurement of early changes in retinal vasculature that are not detectable during routine clinical examination. Abnormalities of retinal arterioles found by rtx1™examination should be considered as a strong risk factor for cardiovascular changes resulting from overweight and obesity.